Evaluating and measuring carbon footprint of the inland operations activity for MAERSK LINE, UK - Kadawala, Jatin (2009)
The emissions of greenhouse gases (GHG) but the foremost carbon-dioxide (CO2), is beginning human induced climate change have turned out to be a global and ominous issue. All participants, society, groups etc ought to be betrothed in the mission of mitigating the anticipated impacts. For any business organisation determined to deal with the issue, measuring its carbon footprint is an indispensable footstep to take. Since 2003, A.P.Moller Maersk group has monitored the level of CO2 emissions associated from their ship‟s operations for carrying freight cargoes from one port to the other. The scope of this study is to measure CO2 emissions originating from fuel consumption from their UK landside operations i.e. movement of container from port to inland locations or consignee sites and other facilities and back to port. During the last year the emissions figures from ships have been published in their annual sustainability report and also published in shipping news, from which it is evident that MAERSK group have managed to reduce the group‟s total CO2 emissions. These are in lines with the projected CO2 reduction targets, and in a carbon constrained future it will be seen as a competitive advantage for an organisation to continue on this route. Carbon-dioxide emissions from the landside transportation of freight containers have so far been kept outside the monitoring scope. These sources are likely to contribute significantly to the total carbon impact of a leading multinational liner shipping company like MAERSK LINE, and hence they should also be screened, monitored and managed. In this report of carbon-dioxide emissions accounting, MAERSK LINE freight transports are examined. The identification of emission sources, the handling of transport activity data, the application of proper emissions calculation methodologies and organisational aspects. 4 Emissions calculations are carried out for two specific intermodal systems managed by MAERSK LINE; the Road Freight and the Rail Freight Transport System. The road and rail freight transports, operates within the UK for the distribution of import consignment and collecting export loads which are moved in full container loads. It is estimated to contribute with 126,583 tonnes CO2 during 2008. Since the system is not optimised to a reasonable degree between rail and road transport systems, the CO2 impact per tonne-km is relatively low for rail mode of transportation. Over the same period the road freight‟s estimated CO2 emissions are 100,707 tonnes. Together these transport activities contributes to about 3 percent of the MAERSK LINE‟s total CO2 based on the reporting of 2006. The potential for carbon-dioxide (CO2) reductions is covered by two possible change-oriented case studies. It can be concluded that short-sea transportation seldom is an alternative to road transports. Intermodal transports combining road and rail can, depending on the circumstances, reduce the CO2 impact considerably compared to only using road transports. Reducing transportation work by optimising a transport activity has been viewed as the best option for CO2 reductions. Resolution should be put into reducing the need for road freight transports, considering a high emissions level per tonne-km. Monitoring emissions for both the transport mode activities that falls under MAERSK‟s responsibility will reduce the risk of sub optimisation. While introducing system alterations in order to reduce CO2 emissions will have a range of implications for all stakeholders / actors involved. Further, effects on lead-time, costs and storing capacity are some of the factors that will have to be further analysed and examined. Other constraints to introducing system changes could require of knowledge, resources and available transport options.